EXPRO (EXAM PROCTORING) : SISTEM MONITORING KEBISINGAN KECURANGAN UJIAN BERBASIS ESP32 DENGAN MIKROFON GY-MAX9814 TERINTEGRASI TELEGRAM - Sheva Nurhaliza (2024)
The rapid development of information technology cannot be avoided by the world of education (Andriani, 2016). One indicator of educational success is integrity in the examination process, where every examinee must be guaranteed to be honest, fair and without cheating. Unfortunately, exam cheating is still a challenge faced by the education system in Indonesia. The most common forms of cheating in exams are discussing and asking friends (Musthofa, et al, 2021). In addition, the Minister of Environment Decree no. 48 on Noise Level Standards in the School Environment, which stipulates that the maximum noise level in classrooms is 55 decibels (dB). EXPRO (Exam Proctoring) is an ESP32-based exam cheating noise detector with automatic notification that can provide notification to the exam supervisor in the form of a message in the telegram application if the noise exceeds the maximum limit. EXPRO is designed using an ESP32 microcontroller as the main microcontroller, then there is a GY-MAX9814 sensor as an additional component. The test results show that EXPRO is able to detect noise with sufficient accuracy with a GY-MAX9814 sensor error rate of 0.4% and an accuracy of 99.5%. Through integration with IoT technology, this tool can provide automatic notifications to exam invigilators in real-time, enabling invigilators to take action quickly in overcoming exam cheating.